Immunopurification of Human Factor VIII/vWF Complex from Plasma - Mejan, Odile; Fert, Vincent; Delezay, Maryléne; Delaage, Michel; Cheballah, Rose; Bourgois, Alain (Thrombosis and Haemostasis, 1988)
In this study we describe a process for immunopurification of FVIII/vWF complex directly from plasma. A mAb against vWF has been selected that is able to bind, under physiologic conditions, the FVIII/vWF complex and to release it in slightly alkaline conditions while preserving its activity.After investigating the influence of solid supports and of coupling methods on the recovery of active FVIII we produced an immunoadsorbent by immobilisation of the selected mAb onto a Sephacryl S-1000 support using a benzoquinone coupling method. With this immunoadsorbent we developed a purification process directly from plasma with an excellent recovery (50%) of both FVIII and vWF activities. The product obtained is very enriched (the FVIII: C specific activity is 20 IU/mg of protein) and is stable after lyophilization.
Keywords: Factor VIII; von Willebrand factor; Monoclonal antibodies; Immunopurification; Immunoadsorbent